(untitled) (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2025)
Indonesia's tropical climate, influenced by high temperatures and humidity, accelerates corrosion processes, especially in industrial and marine environments. Numerous studies have explored natural materials as corrosion inhibitors; however, most organic inhibitors suffer from poor thermal stability due to degradation of their chemical structures. This study aims to develop a heat-resistant and eco-friendly corrosion inhibitor using modified glucomannan from Amorphophallus onch (porang flour). The modification included using periodate oxidation to create an intermediate compound (GA-1), and then reacting it with para-aminobenzoic acid (pABA) to form a yellow-colored product. The synthesized compound was evaluated for its corrosion inhibition activity on mild steel in artificial seawater using various immersion times. At a concentration of 0.5 mg/L, the inhibitor exhibited an efficiency of 93.74% after 12 hours, decreasing slightly to 92.06% after 24 hours and 89.65% after 36 hours. The way it works is thought to be by the compound sticking to the steel surface, creating a protective layer that prevents harmful ions from interacting with the metal and slows down both the rusting of the metal and the reactions involving oxygen. These results indicate that the glucomannan–pABA derivative is a potentially effective eco-friendly corrosion inhibitor that can be used in tropical areas where corrosion is a problem.